The handbook of global trade policy - Klasen, Andreas (Hoboken, NJ John Wiley & Sons, 2020)
"Global trade is a key driver for economic growth, and trade is related to several dimensions: The Fourth Industrial Revolution (4IR) with disruptive technologies, globalisation of markets, innovation leading to new trade opportunities, as well as foreign investments following exports lead to both challenges and opportunities for companies being active in cross-border business. Digital technologies are changing the business environment at breathtaking speed; exports are important drivers to increase economies of scale, boost sales volumes and diversify companies' customer base; and foreign direct investment (FDI) can substantially yield competitive advantages for firms. From an economic perspective, growth is powered by innovation, investments and exports, helping both industrialised and developing countries to reduce poverty and prosper"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Commercial policy; International economic relations; International trade